Multicore Processors and Systems - Keckler, Stephen W.; Olukotun, Kunle; Hofstee, H. Peter (Integrated Circuits and Systems,, 2009)
Multicore Processors and Systems provides a comprehensive overview of emerging multicore processors and systems. It covers technology trends affecting multicores, multicore architecture innovations, multicore software innovations, and case studies of state-of-the-art commercial multicore systems. Cross-cutting themes of the book are the challenges associated with scaling up multicore systems to hundreds of cores. The architecture chapters focus on innovative multicore execution models as well as infrastructure for multicores, including memory systems, on-chip interconnections, and programming models. The case studies examine multicore implementations across different application domains, including general purpose, server, media/broadband, and signal processing. The authors of the chapters include leaders in the research of multicore architectures as well as designers responsible for the implementation of commercial multicore systems. Researchers and practitioners will appreciate the projection of technology trends and its expected impact on multicore system design. The case studies throughout the book serve to provide insight into different approaches of designing multicore systems that will give the reader benefit of first-hand experience from the original innovators. Because of its emphasis on both fundamentals and on case studies, this book can serve as a primary textbook for an advanced course in parallel and multicore system design.